Translator of malay text to Kod Tangan Bahasa Melayu - Muharam, Monalissa (2007)
Communication is very important to human being. Even for the Deaf and Mute community. They were using sign language to communicate between them, also with normal people. Sign language is a language of hand shapes, facial expressions and movement used as a form of communication. However, current learning method cannot make them interesting to learn and understand the sign language. Because of that, Vivid Splendour takes this opportunity to develop software that will help hearing impaired to learn Manually Coded Malay. This software is developed for primary school students for special education. This dictionary contains over 800 entries in Manually Coded Malay. i-KOD was develop by using Waterfall with prototyping methodology. The software is fully developed using Visual Basic combined with other multimedia authoring tools, such as Sony Vegas (video and sound editor) and Adobe Photoshop (image editor). From a recent survey done on 74 students of the hearing-impaired it was found that 86.5% who use i-KOD pass the test that was given. This shows the usefulness of using multimedia elements in learning and education process at special school for hearing-impaired students.